Protective effects of flavonoids from Coreopsis tinctoria Nutt. on experimental acute pancreatitis via Nrf-2/ARE-mediated antioxidant pathways. (5th October 2018) - Du, Dan; Yao, Linbo; Zhang, Rui; Shi, Na; Shen, Yan; Yang, Xinmin; Zhang, Xiaoying; Jin, Tao; Liu, Tingting; Hu, Liqiang; Xing, Zhihua; Criddle, David N.; et al.
Abstract: Ethnopharmacological relevance: Oxidative stress is a prominent feature of clinical acute pancreatitis (AP). Coreopsis tinctoria has been used traditionally to treat pancreas disorders like diabetes mellitus in China and Portugal and its flavonoid-rich fraction contain the main phytochemicals that have antioxidant and anti-inflammatory activities. Aim of the study: To investigate the effects of flavonoids isolated from C. tinctoria on experimental AP and explore the potential mechanism. Materials and methods: LC-MS based online technique was used to analyse and isolate targeted flavonoids from C. tinctoria . Freshly isolated mouse pancreatic acinar cells were treated with taurocholic acid sodium salt hydrate (NaT, 5 mM) with or without flavonoids. Fluorescence microscopy and a plate reader were used to determine necrotic cell death pathway activation (propidium iodide), reactive oxygen species (ROS) production (H2-DCFDA) and ATP depletion (luminescence) where appropriate. AP was induced by 7 repeated intraperitoneal caerulein injections (50 μg/kg) at hourly interval in mice or retrograde infusion of taurolithocholic acid 3-sulfate disodium salt (TLCS; 5 mM, 50 μL) into the pancreatic duct in mice or infusion of NaT (3.5%, 1 mL/kg) in rats. A flavonoid was intraperitoneally administered at 0, 4, and 8 h after the first caerulein injection or post-operation. Disease severity, oxidative stress and antioxidant markers were determined. Results: Total flavonoids extract and flavonoids 1–6 (C1 -C6 ) exhibited different capacities in reducing necrotic cell death pathway activation with 0.5 mM C1, (2 R, 3 R)-taxifolin 7-O- β -D-glucopyranoside, having the best effect. C1 also significantly reduced NaT-induced ROS production and ATP depletion. C1 at 12.5 mg/kg and 8.7 mg/kg (equivalent to 12.5 mg/kg for mice) significantly reduced histopathological, biochemical and immunological parameters in the caerulein-, TLCS- and NaT-induced AP models, respectively. C1 administration increased pancreatic nuclear factor erythroid 2-related factor 2 (Nrf2) and Nrf2-medicated haeme oxygenase-1 expression and elevated pancreatic antioxidant enzymes superoxide dismutase and glutathione peroxidase levels. Conclusions: Flavonoid C1 from C. tinctoria was protective in experimental AP and this effect may at least in part be attributed to its antioxidant effects by activation of Nrf2-mediated pathways. These results suggest the potential utilisation of C. tinctoria to treat AP. Graphical abstract: fx1